Prenatal alcohol exposure is associated with early motor, but not language development in a South African cohort. Issue 3 (6th June 2020) - Hendricks, Gaironeesa; Malcolm-Smith, Susan; Stein, Dan J.; Zar, Heather J.; Wedderburn, Catherine J.; Nhapi, Raymond T.; Chivese, Tawanda; Adnams, Colleen M.; Donald, Kirsten A.
Abstract: Objective: To investigate the association of prenatal alcohol exposure (PAE) and early neurodevelopment in the first 2 years of life, adjusting for maternal socio-demographic and psychosocial factors, in the Drakenstein Child Health Study (DCHS), a South African birth cohort study. Methods: The DCHS comprises a population-based birth cohort of 1143 children, of which a subsample completed the Bayley Scales of Infant Development-III (BSID-III) at 6 ( n = 260) and 24 months of age ( n = 734). A subset of alcohol-exposed and -unexposed children was included in this analysis at age 6 ( n = 52 exposed; n = 104 unexposed) and 24 months ( n = 92 exposed; n = 184 unexposed). Multiple hierarchical regression was used to explore the associations of PAE with motor and language development. Results: PAE was significantly associated with decreased gross motor [odds ratio (OR) = 0.16, 95% confidence interval (CI) = 0.06–0.44, p = 0.001] or fine motor (OR = 0.16, 95% CI = 0.06–0.46, p = 0.001) functioning after adjusting for maternal socio-demographic and psychosocial factors at 6 months of age only. No significant effects were found in either receptive or expressive communication and cognitive outcomes at either time points. Conclusion: PAE has potentially important consequences for motor development in the first 2 years of life, a period during which the most rapid growth and maturation occur. These findings highlight the importance of identifying high-risk families in order to provide preventive interventions, particularly in antenatal clinics and early intervention services.